Progressive Fahr's Syndrome with Severe Hypocalcemia in a Woman with Uncontrolled Type 2 Diabetes Mellitus and Coronary Artery Disease: A Case Report - Luh Wayan Puspa Ningsih; Ida Bagus Kade Satyagraha (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Fahr's syndrome denotes bilateral, symmetric calcification of the basal ganglia and other deep cerebral structures arising from an identifiable secondary cause, most commonly a disorder of calcium–phosphate metabolism. Its association with diabetes mellitus and systemic vascular calcification is increasingly recognized but seldom documented in a single patient. Case presentation: A 58-year-old woman presented with one month of intermittent confusion, bilateral resting hand tremor, intermittent muscle cramps, and gait imbalance. Three months earlier she had a first-ever generalized tonic–clonic seizure coinciding with a new diagnosis of type 2 diabetes mellitus, after which she was non-adherent to insulin therapy. Examination revealed a fine resting tremor, a positive Trousseau sign, and impaired finger-to-nose testing. Investigations showed severe hypocalcemia (4.4 mg/dL), HbA1c 9.7%, and electrocardiographic anterior ischemia with cardiomegaly on chest radiography. Non-contrast cranial computed tomography demonstrated extensive bilateral symmetric calcification of the basal ganglia, cerebellum, thalami, and corona radiata–centrum semiovale. She was diagnosed with Fahr's syndrome with hypocalcemia, type 2 diabetes mellitus, and coronary artery disease, and managed with insulin, calcium lactate, vitamin D3, aspirin, simvastatin, and bisoprolol, with symptomatic improvement by the third hospital day. Conclusion: Bilateral intracranial calcification warrants a structured search for secondary causes, particularly calcium–phosphate disturbance. The coexistence of uncontrolled diabetes, coronary artery disease, and progressive brain calcification supports a panvascular contribution and underscores the need for sustained metabolic control and longitudinal neurological follow-up, given that no curative therapy currently exists.